Hierarchical Piezoresponse in Collagen. Issue 4 (1st December 2021) - Cartwright, Victoria F.; Brown, Cameron P.
Abstract: The piezoelectric nature of collagen has been known for decades, yet its manifestation across, and interactions between, hierarchies remains elusive. Here, piezoelectricity at the tropocollagen‐, microfibril‐, and fibril‐level hierarchies is examined experimentally, using collagen assembled from solution onto muscovite mica substrates. An amplification of the d 15 response of 35–50% is observed between the tropocollagen and fibril levels, with no difference observed between the microfibril and fibril levels. Comparison of experimental results with simulation indicates the potential to optimize collagen piezoresponse via tropocollagen packing to exceed the piezoelectric properties of native collagen fibrils. By improving electromechanical performance through adjustments to winding angle and packing, it may therefore be possible to utilize collagen in low‐cost, biodegradable, and biocompatible sensing or harvesting devices. Abstract : Hierarchical piezoresponse in type 1 collagen is investigated by directed self‐assembly on muscovite mica substrates. An enhancement of 35–50% is observed in the d15 coefficient between the tropocollagen and fibril levels. This indicates opportunities for the improvement of collagen‐based piezoelectric harvesting and sensing devices through the manipulation of tropocollagen packing structure, in addition to its intrinsic piezoresponse.